The Epidemiology and Effect of Sliding Injuries in Major and Minor League Baseball Players. (August 2017) - Camp, Christopher L.; Curriero, Frank C.; Pollack, Keshia M.; Mayer, Stephanie W.; Spiker, Andrea M.; D'Angelo, John; Coleman, Struan H.
Background: Although sliding occurs frequently in professional baseball, little is known about the epidemiology and effect of injuries that occur during sliding in this population of elite athletes. Purpose: To describe the incidence and characteristics of sliding injuries, determine their effect in terms of time out of play, and identify common injury patterns that may represent appropriate targets for injury prevention programs in the future. Study Design: Descriptive epidemiologic study. Methods: All offensive sliding injuries occurring in Major League Baseball (MLB) and Minor League Baseball (MLB) that resulted in time out of play during a span of 5 seasons (2011-2015) were identified. In addition to player demographics, data extracted included time out of play, location on field where injury occurred, level of play, treatment (surgical vs nonsurgical), direction of slide (head vs feet first), body region injured, and diagnosis. Descriptive statistics were used to describe the distribution of these injuries, and injury rates were calculated per slide. Results: From 2011 to 2015, 1633 injuries occurred as a result of a slide. The total number of days missed per season was 4263. Surgical intervention was required for 134 (8.2%) injuries, and the mean days missed was 66.5 for players treated surgically and 12.3 days for players treated nonoperatively ( P < .001). MLB players were more likely than MiLB players to require surgical intervention (12.3% vs 7.5%, P = .019). Injuries to the hands/fingers represented 25.3% of all injuries and 31.3% of those requiring surgery. Although the majority of injuries occurred at second base (57%), the per-slide injury rate was similar across all bases ( P = .991). The estimated overall frequency of injury in MLB was once per every 336 slides, and the rate of injury for head- and feet-first slides was 1 in 249 and 413 slides, respectively ( P = .119). Conclusion: Injuries occurring while sliding in professional baseball result in a significant amount of time out of play for these elite athletes. Injuries occurring at second base and those occurring to the hands and fingers were most prevalent and may be an appropriate target for future injury prevention programs.